Molecular detection and phylogenetic analysis of Anaplasma platys-like and Candidatus Anaplasma boleense strains from Argentina - Sebastian, Patrick (2023)
The present study aimed at the molecular detection of Anaplasma spp. in different samples obtained from cattle, goats and free-living Rhipicephalus microplus ticks from Argentina. DNA of members of the Anaplasmataceae family was detected by different PCR assays. The phylogenetic analyses of the obtained partial DNA sequences of the 16 S rDNA gene resulted in the identification of two different Anaplasma spp.: (I) Anaplasma platys-like bacteria (in blood sample from cattle and pools of R. microplus larvae and (II) Candidatus Anaplasma boleense (in blood samples from goats and one pool of R. microplus larvae of R. microplus). Candidatus A. boleense was found in two provinces that belong to different biogeographic regions, which leads to the conclusion that this bacterium may be widely distributed in Argentina. Interestingly, both Anaplasma spp. were found in the same R. microplus population in Chaco province, indicating that these two strains of Anaplasma are circulating in the same tick population. The results of this work represent the first report of the circulation of A. platys-like bacteria and Ca. A. boleense in domestic ruminants and free-living R. microplus ticks in Argentina. Further studies to determine the prevalence of infection, dispersion, clinical impact, transmission routes and cross-reactivity in serological tests of both Anaplasma species are needed.